State Fiscal Policies and Regional Economic Activity - Matthias Uhl (Philipps-University Marburg, Faculty of Business Administration and Economics, 2014)
In this paper, I estimate a structural panel vector autoregression to study the consequences of changes in U.S. state government fiscal policies for local economic activity in the short-term. My main result is that the state-level spending multiplier is relatively small and the tax multiplier relatively large. After four years, the government spending multiplier is 0.6 and the tax multiplier -2.62. This conclusion is found to be robust across different model specifications. I also find that both state spending and state revenue shocks increase out of state output.
Keywords: E62; H30; R50; 330; Spending multiplier; Tax multiplier; Subnational government